Higher parity is associated with lower mortality in a European population of women with high fertility: results from Ireland. - Mc Garrigle, Christine; Kenny, Rose (My University, 2021)
Research has often found a U- or J-shaped association between parity and mortality. Many researchers have suggested repeated pregnancy, childbirth, and lactation taxes the body beyond a certain parity level. Available research has concentrated on populations with controlled fertility or historic populations. Ireland presents an opportunity to explore these associations in a modern sample with high fertility. We use data from the Irish Longitudinal Study on Ageing (TILDA) to test whether parity is associated with mortality in women aged 50 years or over (n = 4177). We use Cox proportional hazards models to model survival and adjust for demographics and early life circumstances. We test whether a number of health characteristics mediate these effects. Models were also stratified by birth cohort to test possible cohort effects. Higher parity was associated with lower risk of mortality, even after adjustment for early life and socioeconomic circumstances. This effect was not mediated by current health characteristics. The effects were largely driven by those born between 1931 and 1950. Increasing parity is associated with decreasing mortality risk in this sample. The effects of parity could not be explained through any of the observed health characteristics. These findings are in contrast to much of the literature on this question in similar populations. Lack of fertility control in Ireland may have "selected" healthier women into high parity. Social explanations for these associations should be further explored.
PUBLISHED
Keywords: Ireland, Mortality, Parity, Women; Ageing